Utilization of employee wellness program by the staff members at Natalspruit Hospital - Manamela, Makgabo Johanna (My University, 2011)
Background: In 2006 the Gauteng Department of health endorsed a Wellness Program Policy. The policy was introduced and implemented in all Gauteng Province Hospitals. The policy spells out the integrated model of wellness program. The focus is to promote wellness, healthy lifestyle and assist the staff members who are ill while at work place. The department found it crucial to ensure that the staff members are well cared for in order to be productive. Aim: To describe the utilization of the various components of the wellness program by the staff members and to describe the outcome thereof. Methodology: The research design was a quantitative, cross sectional retrospective record review. The analysis focused on the records of the staff members of Natalspruit Hospital, who utilized the wellness program services from January to December 2009. The scope of the study covered all five components of wellness program as outlined by the Gauteng Department of Health Wellness Program Policy. Data was collected and analysed from 941 entries in the Wellness Clinic records. Conclusion: This research found that the average number of staff visits during the study period was 80.1(SD 22.1) which represents 80% of the total staff complement and that actual percentage of staff who utilized the service is much lower. However during the last month of the period under study attendance rate represented 5.8% of total staff establishment. The majority of the staff members were women (90%); female subjects were significantly younger than male subjects, p <0.01 (Mann Whitney’s test). The most professional and occupational categories that used the services were the nurses. The components that were mostly utilised was Birth control (48.9%); specifically for family planning, followed by the Occupational Health and Safety component in the area of Hepatitis B (11.5%) and needle prick (3.9%). The majority of the staff members continued with the services in the clinic (86.9%) while very few staff members were referred out of the clinic (5.3%) to the casualty/ out- patient department, court and ICAS. Only (7.76 %) of cases were resolved. The majority of the staff members utilized the organization and climate for management of health related problems component, especially in the services of birth control for family planning section. It seems a waste of resources to have an entire wellness program where staff members are mostly using it primarily for family planning, therefore the research described the basic requirements for effective EWP and also the importance of capacity needed for effective policy management, then suggested the comprehensive components. The report findings could benefit the Government in planning and operations of other Wellness Programs across the country.
Keywords: employees wellness programmes